Design of Children's Game "Buddhist Relics" to Introduce the History of Civilization and Culture in Borobudur Temple - Amelia Eka Pratiwi; Zephan Ali Yafi; Sartono Sartono (Journal of Multimedia Trend and Technology, 2023)
Borobudur is one of the historical heritages in the world whose beauty can still be enjoyed and the history of the founding of the Borobudur temple and its relics can also be identified. Not all people in Indonesia know the geographical location of Borobudur temple, let alone what historical heritage is in the Borobudur area, it can be used as a game to attract the interest of the younger generation to find out about cultural heritage and preserve it so that it is not lost to the erodes of time. Borobudur Temple has a story message for its people, namely a story about the teachings of norms, morals, and morals that humans must have in everyday life. Apart from that, the development of games in Indonesia is increasingly popular. It is not only a medium of entertainment but can also be a medium of education for its users. With this foundation, the author created an educational game about the relics of the Borobudur temple with the game title "Treasure in Borobudur". The aim is so that children in Indonesia do not forget history along with the rapid development of technology.